Development of Beak in chicken embryo - Haider Ali Nasser (Genius Journals, 2021)
The beak in chickens is a common organ between the two systems (digestive and respiratory). The beak consists of two parts, an inner bony part, and an outer, leathery paired part with flat cells strongly connected to each other. 60 fertilized eggs were collected and divided into two groups, with 30 eggs for each group. The eggs were then placed in the incubator at a temperature of 37°C for a period of two weeks and samples were taken for histological study. The results showed that the beak consists mainly of the ectoderm, but the rest of the layers participate in its composition as well, where the beak developed into two parts in the first week of incubation of chicken eggs
Keywords: Beak; respiratory system